2020
DOI: 10.1002/da.23042
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive predictors of self‐reported reward responsivity and approach motivation in depression: A data‐driven approach

Abstract: Background: Individual differences in reward-related processes, such as reward responsivity and approach motivation, appear to play a role in the nature and course of depression. Prior work suggests that cognitive biases for valenced information may contribute to these reward processes.Yet there is little work examining how biased attention, processing, and memory for positively-and negatively-valenced information may be associated with reward-related processes in samples with depression symptoms. Methods:We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 71 publications
2
6
0
Order By: Relevance
“…Moreover, moderator analyses revealed that the respective effect sizes became progressively larger as depressive symptom severity increased, suggesting that depressed individuals' devaluation of positivity and facilitatory endorsement of negativity becomes more pronounced as symptom severity increased. This is consistent with prior work demonstrating that depressed individuals process positive information in a biased manner (Hsu et al, 2020;McNamara et al, 2021) and may point to a more specific mechanism of devaluation of the self, as initially hypothesized when reward devaluation theory was introduced (Winer & Salem, 2016). By comparison, depressed individuals did not differ from nondepressed individuals on the endorsement of positive words and the endorsement of negative words when describing others.…”
Section: Endorsementsupporting
confidence: 89%
“…Moreover, moderator analyses revealed that the respective effect sizes became progressively larger as depressive symptom severity increased, suggesting that depressed individuals' devaluation of positivity and facilitatory endorsement of negativity becomes more pronounced as symptom severity increased. This is consistent with prior work demonstrating that depressed individuals process positive information in a biased manner (Hsu et al, 2020;McNamara et al, 2021) and may point to a more specific mechanism of devaluation of the self, as initially hypothesized when reward devaluation theory was introduced (Winer & Salem, 2016). By comparison, depressed individuals did not differ from nondepressed individuals on the endorsement of positive words and the endorsement of negative words when describing others.…”
Section: Endorsementsupporting
confidence: 89%
“…Patients with depression show reduced activation of both reward and self-related areas of the brain when processing positive stimuli (Northoff, 2007; Northoff & Hayes, 2011). Reduced self-referential processing of positive information has also been identified as the most robust predictor of low approach motivation and reward responsivity (Hsu et al, 2020). Increased sensitivity to punishing feedback may sustain preferential processing of negative information about the self, reinforcing negative self-schema.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our hypothesis, individuals engaging in NSSI are more likely to rate negative adjectives as more relevant to themselves and positive adjectives as less relevant to themselves compared with the controls. Considerable evidence indicates that biased self-referential processing is closely related to dysfunctional coping strategies ( Hsu et al, 2020 , Mennin and Fresco, 2013 ). In particular, negative self-referential processing facilitates cognitive and emotion regulation deficits and, in turn, leads to maladaptive behavioral responses to unwanted emotional stimuli ( Frewen et al, 2020 , Mennin and Fresco, 2013 , Renna et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%